Deficiency in mTORC1‐controlled C/EBPβ‐mRNA translation improves metabolic health in mice. (25th June 2015) - Zidek, Laura M; Ackermann, Tobias; Hartleben, Götz; Eichwald, Sabrina; Kortman, Gertrud; Kiehntopf, Michael; Leutz, Achim; Sonenberg, Nahum; Wang, Zhao‐Qi; von Maltzahn, Julia; Müller, Christine; Calkhoven, Cornelis F
Abstract The mammalian target of rapamycin complex 1 (mTORC1) is a central regulator of physiological adaptations in response to changes in nutrient supply. Major downstream targets of mTORC1 signalling are the mRNA translation regulators p70 ribosomal protein S6 kinase 1 (S6K1p70) and the 4E‐binding proteins (4E‐BPs). However, little is known about vertebrate mRNAs that are specifically controlled by mTORC1 signalling and are engaged in regulating mTORC1‐associated physiology. Here, we show that translation of the CCAAT/enhancer binding protein beta (C/EBPβ) mRNA into the C/EBPβ‐LIP isoform is suppressed in response to mTORC1 inhibition either through pharmacological treatment or through calorie restriction. Our data indicate that the function of 4E‐BPs is required for suppression of LIP. Intriguingly, mice lacking the cis‐regulatory upstream open reading frame (uORF) in the C/EBPβ‐mRNA, which is required for mTORC1‐stimulated translation into C/EBPβ‐LIP, display an improved metabolic phenotype with features also found under calorie restriction. Thus, our data suggest that translational adjustment of C/EBPβ‐isoform expression is one of the key processes that direct metabolic adaptation in response to changes in mTORC1 activity.